Molecular, morphometric, and spatial data analyses provide new insights into the evolutionary history of the Peromyscus boylii species complex (Rodentia: Cricetidae) in the mountains of Mexico. Issue 1 (31st December 2022) - León-Tapia, M. Ángel; Rico, Yessica; Fernández, Jesús A.; Espinosa de los Monteros, Alejandro
Abstract : Peromyscus is the most speciose genus in America, which occupies almost every terrestrial habitat type. However, its taxonomy and evolutionary relationships remain unsolved in several species, one species group with these issues is the P. boylii complex. This complex consists of 11 species ( P. beatae, P. boylii, P. carletoni, P. ensinki, P. greenbaumi, P. kilpatricki, P. levipes, P. madrensis, P. schmidlyi, P. simulus, and P. stephani ) largely distributed in Mexico and has been taxonomically studied during the last 40 years, resulting in the description of new species, several of them from the mountains of central Mexico. In this study, we aimed to integrate molecular, morphometric, and spatial data analysis approaches to inquire into the phylogenetic relationships. To clarify the taxonomic status of the P. boylii complex, particularly for the species distributed in the central Mexican highlands where the taxonomic uncertainty is high. We performed phylogenetic and divergence time analyses based on four molecular markers for all species within the complex, we explored cranium shape and size variation in 146 individuals of continental species ( P. madrensis and P. stephani excluded) using geometric morphometrics. Also, we evaluated environmental differentiation and ecological niche modeling analyses of three species endemic to the central Mexican highlands to retrieve evidence on their evolutionary history. Our results recovered one well-supported clade including all mountainous species, in which P. schmidlyi was sister to the clade composed of P. greenbaumi and P. ensinki, which diverged during the late Pleistocene. The novel morphological data allowed a better differentiation of all continental species. The discovery of new specimens for P. greenbaumi and P. ensinki improved their taxonomic knowledge, as well as delimiting their habitat and distribution, showing substantial environmental divergence with low overlapped geographical distributions; P. schmidlyi restricted to the Sierra Madre Occidental, P. ensinki to the central-west Trans-Mexican Volcanic Belt, and P. greenbaumi to the center of the Sierra Madre del Sur. We discuss the biogeographic history of these three lineages and the role of the late Pleistocene climatic oscillations on their diversification.